Indicadores de mobilidade urbana sustentável para a cidade de Uberlândia, MG - Assunção, Miriellen Augusta da (2012)
To the extent that environmental, economical and social problems are responsible for the decline of the quality of life in the cities it is necessary to deploy sustainable measures, as well as to monitor the elements that characterize the urban environment. Thus, indicators of mobility have become basic instruments to promote the knowledge and the information for understanding the particularities presented in the urban areas. The main objective of this research was to identify indicators of urban mobility for city of Uberlândia, MG, by utilizing the Index of Sustainable Urban Mobility IMUS, a tool of analysis of sustainable urban mobility. The specific objectives aimed at to appraise sustainable development, to understand urban mobility, to identify sustainable urban mobility and the accessibility, to define indicators of sustainable mobility, to calculate the IMUS for city of Uberlândia and to evaluate the results. 80 out of the 87 indicators defined by the Guide of Indicators of the IMUS were calculated. The score found for Global IMUS, 0.717, in a scale that goes from 0,00 the 1,00, can indicate that the city has adopted public policies favorable to urban mobility. The main aspects that indicate the concern with sustainable urban mobility are the Social and Ambiental aspects and Accessibility. However, the domain not Motorized Modes contributed less for urban mobility in Uberlândia, by verifying that there are no parking lots for bicycles in public transportation terminals, as well as it is reduced the number of exclusive lanes for bikes and paths for pedestrians in the city. The result from IMUS can be an important instrument for the deployment of public policies that add improvements for the urban mobility and accessibility and its computation can be improved embracing new indicators in future works.